The Relationship between Language Skills and Social Communication Abilities in Children with Autism Spectrum Disorder in Surakarta - Hefny, Yasmin Advira; Muryanti, Muryanti; Susanti, Nadya (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Language skills play an important role in the development of children's social skills, especially in children with Autism Spectrum Disorder (ASD). This study aims to analyze the relationship between language skills and social communication skills of children with ASD in Surakarta. This study used a quantitative method with an observational design and a cross-sectional approach. Data were collected through observation and analyzed using univariate and bivariate statistical tests with the help of SPSS 21.0. The results of the analysis showed that there was a significant relationship between language skills and social communication skills of children with ASD, with a significance value of ρ of 0.00 (ρ <0.050) and a correlation coefficient (r) of 0.740. This shows that the higher the child's language skills, the better their social communication skills. There is a significant positive relationship between language skills and social communication skills of children with ASD in Surakarta. Improving language skills can contribute to the development of social communication of children with ASD.